Hospitalist Infectious Disease Service in Academic Medical Centers: A Win-Win for Hospitalists and Fellows. Issue 9 (September 2018) - Townsend, Jennifer; Vishnupriya, Kittane Srinivas; Klein, Eili; Spoelhof, Brian; Zenilman, Jonathan
Abstract : Supplemental digital content is available in the text.